CURRICULUM FOR MULTICULTURAL ISLAMIC EDUCATION AND RELIGIOUS MODERATION AT JAMBUDESA PUBLIC ELEMENTARY SCHOOL - Annisa Nur Baeti; Muhammad Bintang Satriawan; Nuita Alifia Hasanah (Jurnal Konseling Pendidikan Islam, 2026)
This study develops a comprehensive multicultural Islamic education curriculum grounded in religious moderation principles, specifically designed for SD Negeri 1 Jambudesa a rural elementary school in a religiously diverse community. Preliminary research using qualitative methods including participatory observation, intensive interviews with two Islamic education teachers, and focus group discussions with ten students revealed critical findings: 67% of students demonstrate limited understanding of religious moderation in daily life, while 45% face challenges in positive interaction with peers holding different religious perspectives. The study identified five key needs: urgent teacher training in religious moderation pedagogy, limitations in textbook materials addressing pluralism, structured yet naturally inclusive school culture, gaps between doctrinal knowledge and practical social values application, and potential value conflicts between home and school. Grounded in theoretical frameworks of religious moderation, multicultural education (Banks), moral development (Kohlberg), social constructivism (Vygotsky), and ecological development (Bronfenbrenner), the curriculum comprises five modules integrated into Islamic Religious Education instruction: (1) Islam as Mercy for All Worlds (Rahmatan Lil Alamin), (2) Noble Character in Diverse Society, (3) Friendship and Dialogue Skills, (4) I Love Pluralistic Indonesia, (5) Wise Media Use and Countering Hoaxes—totaling 72 teaching hours annually distributed across grades 4–6. Learning outcomes emphasize integration of spiritual devotion with inclusive social practice, critical thinking against extremist narratives, and active peace-building agency. Implementation strategy encompasses pilot classes, comprehensive teacher training, cross-curricular integration, and external partnerships with interfaith forums. Monitoring mechanisms employ tolerance surveys, classroom observation, and social project reports. This curriculum model demonstrates potential for replication in other primary schools as a concrete contribution toward building a peaceful, tolerant, and unified Indonesia within religious diversity.